Compliance To Post Exposure Rabies Vaccination Among Patients Attending Anti - Rabies Clinic in A Tertiary Care Hospital, Bengaluru - Gudegowda, Kishore S; Shivalingamurthy, Ravish K; Vengatesan, Subathra; Sobagiah, Ranganath T; Krishnappa, Anil K (National Journal of Community Medicine, 2016)
Introduction: In India, every 2 seconds a person is bitten and every 30 minutes someone dies from rabies. Complete post-exposure prophylaxis is necessary among the animal bite victims for complete protection. Hence this study aims to determine the patient’s compliance for Intradermal Anti - Rabies Vaccination and also to determine the constraints for compliance. Methodology: A Retrospective record based review was conducted in the Anti - Rabies Clinic of Victoria Hospital, Bengaluru from the month of January to December 2015. The number of study subjects were 2815 after excluding category I cases, rat bite, human bite, re-exposure and pre-exposure cases. The major constraints were found out by interviewing the patient/guardian through the telephone. Results: The compliance rate for Intradermal Rabies Vaccination (IDRV) is 79.60%. The major constraints were distance from the hospital, forgotten the dates, went to their hometown. Conclusion: The compliance rate for rabies vaccination is considerably low for this highly fatal disease. Considering these major constraint factors, the animal bite victims should be motivated effectively through health education at the time of initiation of vaccination course to attain the goal of Rabies free India.